The Dual Hamilton–Jacobi Equation and the Poincaré Inequality - Rigao He; Wei Wang; Jianglin Fang; Yuanlin Li (Mathematics, 2024)
Following the equivalence between logarithmic Sobolev inequalities and hypercontractivity shown by L. Gross, and applying the ideas and methods of the work by Bobkov, Gentil and Ledoux, we would like to establish a new connection between the logarithmic Sobolev inequalities and the hypercontractivity of solutions of dual Hamilton–Jacobi equations. In addition, Poincaré inequality is also recovered by the dual Hamilton–Jacobi equations.